2005
DOI: 10.1088/0957-4484/16/6/050
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of plasma chemistry for dc plasma enhanced chemical vapour deposition of carbon nanotubes and nanofibres

Abstract: The role of plasma in plasma enhanced chemical vapour deposition of carbon nanotubes and nanofibres is investigated with both experimental and computational diagnostic techniques. A residual gas analysis (RGA) of a 12 mbar dc discharge with a C 2 H 2 /NH 3 gas mixture is conducted near the Ni catalyst surface employed for carbon nanofibre growth. The results are corroborated with a 1D dc discharge model that solves for species densities, ion momentum, and ion, electron and neutral gas thermal energies. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 67 publications
8
23
0
Order By: Relevance
“…Also a lot of HCN is observed in our results, which first increases and then drops as a function of CH 4 fraction. We also found that HCN is mainly formed in the bulk plasma region, which is consistent with Hash's results [44]. It is shown in figure 4(b), that the total ion flux again remains almost constant as a function of CH 4 fraction.…”
Section: Effect Of Gas Mixture Ratiossupporting
confidence: 91%
See 1 more Smart Citation
“…Also a lot of HCN is observed in our results, which first increases and then drops as a function of CH 4 fraction. We also found that HCN is mainly formed in the bulk plasma region, which is consistent with Hash's results [44]. It is shown in figure 4(b), that the total ion flux again remains almost constant as a function of CH 4 fraction.…”
Section: Effect Of Gas Mixture Ratiossupporting
confidence: 91%
“…Therefore the fluxes of the various species to the substrate are mainly determined by the ICP power, gas pressure, and gas mixture ratios. The bias power is often applied on the substrate in order to grow aligned CNTs/CNTs [7,16,44,48]. Indeed, it was found that local electric fields are built up near the substrate surface, and control the growth direction of CNTs/CNFs [7,16,44,48].…”
Section: Effect Of Bias Powermentioning
confidence: 99%
“…In addition, a significant amount of atomic nitrogen is also predicted by our model, and this activated nitrogen can also affect the growth kinetics of CNT/CNF at the catalyst surface [53]. Finally, the NH 4 + ions are found to be the dominant ions, which agree well with the simulation results of Hash et al [26,27]. number density (cm In the acetylene/hydrogen plasma (see figure 10), long-chain hydrocarbons such as C 2n H 2 and C 2n H 6 (n=4,…,6) are formed in the discharge, and become important for both pressures.…”
Section: Plasma Chemistry In the Different Gas Mixturessupporting
confidence: 88%
“…Several modeling efforts have been presented in literature to describe the plasma chemistry in various types of plasma reactors used for carbon nanostructure growth, including dc plasmas [73][74][75][76], capacitively coupled rf plasmas [77,78], and inductively coupled plasmas (ICPs) [79][80][81][82][83][84][85]. These are either 0D chemical-kinetics models [79][80][81][82], 1D [73][74][75][76][77][78] or 2D [83][84][85] fluid approaches.…”
Section: (B) Cnts and Related Structuresmentioning
confidence: 99%
“…These are either 0D chemical-kinetics models [79][80][81][82], 1D [73][74][75][76][77][78] or 2D [83][84][85] fluid approaches. The gas mixtures considered in these models are the typical gases used for the growth of CNTs (and other carbon nanostructures), and consist of either CH 4 or C 2 H 2 as hydrocarbon growth precursors, mixed with H 2 or NH 3 as etchant gases, sometimes diluted with Ar.…”
Section: (B) Cnts and Related Structuresmentioning
confidence: 99%